Hough-transform based algorithm for the automatic invariant recognition of rectangular chocolates. Detection of defective pieces. - Montenegro Joo, Javier (2006)
The Hough Transform has been used to develop an algorithm for rotation, translation and size-scaling invariant pattern recognition of polygonal objects. In this research the developed system has been successfully applied to the automatic invariant recognition of rectangular chocolates, including identification of defective samples. Since the entire performance of the resulting system is autonomous, the results may be applied to automatic quality control applications in the industry.